Modelling edge effects at the interface in bonded joints using gradient functions in the mechanical properties of the adhesive: Application of the method to the Arcan test loaded in tension and shear - Benali, A.; Cellard, C.; Sohier, L.; Moretti, A.; Créac'hcadec, R. (International journal of adhesion and adhesives, 2023)
The design of bonded joints requires studies of stress concentrations due to edge effects. For complex joint configurations, the finite element method can be quite costly. The objective is to develop a fast and reliable numerical design tool for bonded assemblies. Therefore, an approach to design bonded assemblies is presented which aims to meet the needs of a design office, particularly in terms of calculation costs. The latter consists in reproducing the edge effects with a single element through the joint thickness using a modulus function. The concept was tested on Arcan specimen with two loading cases: tension (γ = 0°) and shear (γ = 90°). A 2D model under the elastic assumption is developed to describe the edge effects of the joint using Abaqus subroutines (UMat). The approach is set up to solve this problem in the form of two blocks. First, mesh refinement studies for bonded specimens loaded in tension were performed, within a good level of accuracy, on the free edge with the use of local discretization error estimation. After that, the effects of local geometry and modulus ratio are investigated. Afterwards, the von Mises stress at the interface level of the adhesive joint was used to identify a modulus function to describe the behavior of a joint with straight edge geometry for tension and shear loadings. The proposed approach has improved the performance of the model. Actually, the calculation is practically three times faster than for the conventional model. •Numerical equivalence is proposed for the analysis of edge effects in bonded structures.•A numerical analysis is suggested to study the edge effects. This study analyzes the effect geometry and the modulus ratio and estimates reliably the mesh size.•The identification of a modulus function of the adhesive to describe the concentration for tensile and shear loads with a single element through the thickness has been performed.•The accuracy of the method is ≈ 90% and the computational time is reduced by 60%.